ANALISIS PERBANDINGAN BEBAN PAJAK PENGHASILAN TERHUTANG MENURUT PASAL 31E UNDANG UNDANG PAJAK PENGHASILAN DENGAN PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 PADA PT ABC - Widjaja, P Helen; Pratama, Jason (Jurnal Ekonomi, 2017)
This case study analyzed by comparing the income tax payable according to Article 31E of the Income Tax Law and Government Regulation No. 46 Year 2013 on PT Â ABC. In the results of this study prove that according to Government Regulation No. 46 Year 2013 resulted in income tax payable is less than pursuant to Article 31e Income Tax Act